Psychophysiological Responses to a Brief Self-Compassion Exercise in Armed Forces Veterans - Gerdes, Samantha; Williams, Huw; Karl, Anke (Frontiers in Psychology, 2022)
Armed Forces personnel are exposed to traumatic experiences during their work; therefore, they are at risk of developing emotional difficulties such as post-traumatic stress disorder (PTSD), following traumatic experiences. Despite evidence to suggest that self-compassion is effective in reducing the symptoms of PTSD, and greater levels of self-compassion are associated with enhanced resilience, self-compassion in armed forces personnel and armed forces veterans remains under-researched. As a result, it is not known if therapeutic approaches that use self-compassion interventions are an acceptable and effective treatment for this population. Having previously shown that a one-off self-compassion exercise has temporary beneficial psychophysiological effects in non-clinical participants, we conducted this proof-of concept study to investigate whether this exercise is equally beneficial in veterans who had experienced deployment to a combat zone. Additionally, we examined if brief a self-compassion exercise can temporarily reduce hyperarousal symptoms and increase feelings of social connectedness. The current study also investigated the association between PTSD symptom severity, emotion regulation, and self-compassion in 56 veterans. All participants listened to a loving-kindness meditation for self-compassion (LKM-S) and psychophysiological recordings were taken throughout. Psychophysiological effects were observed including heart-rate (HR), skin conductance (SCL), and heart-rate variability (HRV) to determine associations with PTSD and changes in response associated with the self-compassion induction. PTSD symptom severity, dispositional emotion regulation, and self-compassion were measured, and participants also completed state measures of hyperarousal and social connectedness before and after the LKM-S. The findings partially demonstrated that self-compassion can be elicited in a veteran population but there were considerable individual differences in psychophysiological responses. The findings are discussed in light of existing theories of PTSD and self-compassion and the implications of using self-compassion based psychological approaches with veterans.